Global Proteomic Analysis Reveals High Light Intensity Adaptation Strategies and Polyhydroxyalkanoate Production in Rhodospirillum rubrum Cultivated With Acetate as Carbon Source - Bayon-Vicente, Guillaume; Wattiez, Ruddy; Leroy, Baptiste (Frontiers in Microbiology, 2020)
Purple non-sulfur bacteria (PNSBs) are well known for their metabolic versatility. Among them, Rhodospirillum rubrum can assimilate a broad range of carbon sources, including volatile fatty acids (VFAs), such as acetate, propionate or butyrate. These carbon sources are gaining increasing interest in bioindustrial processes since they allow reduction of the production costs. Recently, our lab discovered that, after long term cultivation with acetate as unique carbon source, Rs. rubrum got acclimated to this carbon source which resulted in a drastic reduction of the lag phase. This acclimation was characterized by the amplification of the genomic region containing, among others, genes belonging to the ethylmalonyl-CoA (EMC) pathway, which has been demonstrated to be required for acetate assimilation in Rs. rubrum. In this paper, we combined bacterial growth analysis with proteomic (SWATH -Sequential Windowed Acquisition of All Theoretical Fragment Ion Mass Spectra-processing) investigation to better understand the bacterial response to a sudden increase of the light intensity. We compared the impact of suddenly increasing light intensity on the WT strain to that on the newly described acetate-competent strain in the presence of acetate. Contrary to what was observed with the WT strain, we observed that the acetate-competent strain was tolerant to the light stress. Proteomic analysis revealed that increasing light intensity had a significant impact on the photosynthetic apparatus, especially in the wild-type strain cultivated in the presence of acetate and low concentration of HCO3-. This phenomenon was accompanied by a relatively higher abundance of certain stress related proteins. Our results suggested that the production of PHA, but also potentially of branched chain amino acids synthesis, could be part of the mechanism used by Rs. rubrum to adapt to the light stress and the redox imbalance it triggered.